How Labor Force Participation Mediating Poverty Rate by Others Factors - ROHMAN, Abd. Rohman; PUDJIHARDJO, M.; SUSILO, Susilo (International Journal of Environmental, Sustainability, and Social Science, 2024)
This research examines the factors that influence poverty levels in Indonesia, both directly and indirectly, by analyzing the involvement of labor force participation levels. The study uses BPS data and the APBN Data Portal to evaluate wages, education, and government spending in the education and health sectors as influencing variables. Using time series data, this research form by path analysis aims to identify direct or indirect relationships between variables. The data is first analyzed using descriptive statistical analysis as part of the research methodology. This research using path analysis and the Sobel test, researchers found that education levels only up to junior secondary school have an impact on changes in labor force participation rates but do not have an impact on reducing poverty. In contrast, other variables, such as wages and government spending in the education and health sectors, do not indirectly affect poverty through the labor force participation rate.